THE ROLE OF LOCAL MARKETS IN TRADE RELATIONS BETWEEN CENTRAL ASIA AND RUSSIA (Western European Journal of Historical Events and Social Science, 2025)
This article analyzes the role of local markets in the trade relations of the Central Asian khanates with the Russian Empire in the late 19th and early 20th centuries. It focuses on the structure of local markets in Central Asian cities, methods of product exchange, and the memories of Russian travelers who visited them